MULTI-CRITERIA DECISION MAKING IN STOCK TRADING USING HYBRID FUZZY ANALYTIC HIERARCHY PROCESS EXTENT ANALYSIS - OTHMAN, SHUHADAH (2015)
This research described about a process of multi-criteria decision making in stock trading using hybrid Fuzzy-AHP extent analysis approach. The decision making process is a complex process due to the fact that it will involve more than one criteria that investors need to evaluate or observe in order to ensure the most accurate decision can be made. Due to many criteria involve this research aim to study a Fuzzy-AHP extent analysis method and in multi-criteria decision making process. The method has been adopted to stock trading decision making problem which can provide a recommendation for the decision makers in order to help them maximize a profit. Fuzzy-AHP extent analysis approach includes of evaluation of multiple criteria which at the end will produce an output that may become a reference to the investor/traders during making a decision.